2014
DOI: 10.1155/2014/941514
|View full text |Cite
|
Sign up to set email alerts
|

Fistuloclysis Improves Liver Function and Nutritional Status in Patients with High-Output Upper Enteric Fistula

Abstract: Background. We aimed to determine the efficacy of fistuloclysis in patients with high-output upper enteric fistula (EF). Methods. Patients were assigned into the fistuloclysis group (n = 35, receiving fistuloclysis plus total enteral nutrition (TEN)) and the control group (n = 60, receiving TEN). Laboratory variables were measured during the four-week treatment. Results. At baseline, variables were similar between the two groups. Delta value was defined as the changes from baseline to day 28. Compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(82 citation statements)
references
References 35 publications
0
82
0
Order By: Relevance
“…3 Wu et al found that fistuloclysis could successfully improve liver function and overall nutritional status in patients with high-output enteric fistulae. 2 Ninety-five patients met the entry criteria in this study 2 and were enrolled. They were divided into a control group who received EN only, and a fistuloclysis group who received EN and fistuloclysis.…”
Section: Contrast In the Small Bowel Lumenmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Wu et al found that fistuloclysis could successfully improve liver function and overall nutritional status in patients with high-output enteric fistulae. 2 Ninety-five patients met the entry criteria in this study 2 and were enrolled. They were divided into a control group who received EN only, and a fistuloclysis group who received EN and fistuloclysis.…”
Section: Contrast In the Small Bowel Lumenmentioning
confidence: 99%
“…2 Benefits seen might be because of the improvement in liver function and nutritional status, together with a reduction in fistula output. 2 Up to 70% of patients with fistulae have malnutrition.…”
Section: Contrast In the Small Bowel Lumenmentioning
confidence: 99%
See 3 more Smart Citations